2023
DOI: 10.1039/d3fo01436c
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pectins with different degrees of methyl-esterification and of blockiness in preventing gut epithelial cell barrier disruption and the impact on sodium–glucose co-transporter expression under low and high glucose conditions

Abstract: Pectins support intestinal barrier and have anti-diabetic effects, and can differ in degree of methyl-esterification (DM) and the distribution of non-esterified galacturonic acid residues (DB). Mechanisms and effects of pectin-type...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“… Muñoz-Almagro et al (2021) demonstrated its lipid-lowering effects, reducing cholesterol and triglyceride levels and also highlighted its potential in development of low-glycemic food formulations, which can aid in the prevention and treatment of diabetes. Tang et al (2023) further supported this, showing that LMP can prevent gut epithelial cell barrier disruption and reduce the expression of the sodium-glucose co-transporter, which is involved in glucose transport. They emphasized the stability of LMP in aqueous solutions.…”
Section: Applications Of Pea Pods As Valuable Waste Productsmentioning
confidence: 61%
“… Muñoz-Almagro et al (2021) demonstrated its lipid-lowering effects, reducing cholesterol and triglyceride levels and also highlighted its potential in development of low-glycemic food formulations, which can aid in the prevention and treatment of diabetes. Tang et al (2023) further supported this, showing that LMP can prevent gut epithelial cell barrier disruption and reduce the expression of the sodium-glucose co-transporter, which is involved in glucose transport. They emphasized the stability of LMP in aqueous solutions.…”
Section: Applications Of Pea Pods As Valuable Waste Productsmentioning
confidence: 61%